Dificultad en la lectura y ortografía que afecta la escritura y el habla de los estudiantes del quinto año de educación general básica de la Unidad Educativa María Andrea del cantón Babahoyo, Provincia de Los Ríos - Veliz Jara, Narcisa Cecilia (2020)
Achieving meaningful learning is the goal proposed by each teacher, who tries to teach their classes in the most effective way possible, but this process is affected when there are problems in the classroom that affect students' good performance. Dysortography is a writing disorder that makes it difficult for a child to write a text, they constantly commit many misspellings and sometimes their texts are completely incomprehensible. Under these considerations, an investigation is given where the influence of dysortography on the significant learning of students is determined, for which purpose I carry out the study of the case in students who present deficits in writing by the “María Andrea Educational Unit” in the Canton Babahoyo Province of Los Ríos, with the deductive and inductive method which offers me a direct approach to the problem that is intended to be investigated and known, applying techniques such as the interview, the same observation that aims to obtain information regarding the problems of the students.